The NACA score predicts mortality in polytrauma patients before hospital admission: a registry-based study - Paolo Ivan Fiore; Andrea Stefano Monteleone; Jochen Müller; Giuseppe Filardo; Christian Candrian; Martin Riegger (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2024)
Abstract Background The early assessment of the severity of polytrauma patients is key for their optimal management. The aim of this study was to investigate the discriminative performance of the NACA score in a large dataset by stratifying the severity of polytraumatized patients in correlation to injury severity score (ISS), Glasgow Coma Scale (GCS), and mortality. Methods This study on the Swiss Trauma Registry investigated 2239 polytraumatized patient (54.3 ± 22.8 years) enrolled from 2015 to 2023: 0.5% were NACA 3, 76.7% NACA 4, 21.4% NACA 5, and 1.4% NACA 6. The NACA predictive value of patients’ mortality was investigated, as well as the correlation of ISS and GCS scores, and other factors influencing patients’ survival at discharge and after 28 days. Results In NACA 4 and 5 the survival rate during hospitalization was 97.7% and 82.5%, respectively, and 28-day mortality 3.5% and 23.5%, respectively (p < 0.0005). NACA correlated with GCS in the prehospital phase and in the emergency room (p < 0.0005), as well as with ISS (p < 0.0005). NACA 4 and 5 presented different injury patterns (fall < 3 m vs vehicle accident) with NACA 5 requiring more CPR and intubation (p < 0.001, p < 0.0005). The ROC AUC analysis showed the prehospital NACA and GCS values as the strongest variables predicting patients’ survival. Conclusions This study provides valuable evidence supporting the effectiveness of the NACA score in assessing the severity of polytrauma patients in both the pre-ER and ER condition. Considering the statistical significant correlation with the GCS and with the ISS, NACA is a valid score for assessing polytrauma patients.